Modelo de educação integrativa : a abordagem STEAM em uma proposta de ensino investigativo experienciado em uma escola estadual, Cuiabá, MT - Vuerzler, Hugo Loriano (2020)
In line with the moment of restructuring of the basic education in Brazil, based on educational, progressive and innovative paradigms with which the student is motivated to lead his own learning, the present work, considering the problem of the discouragement of students from a state high school located in the city of Cuiabá, brought as a research question whether Collaborative Active Learning, worked in the context of the STEAM approach, contributes to the process of Scientific Education of those students, in the Nature Sciences, Arts and Mathematics areas. This used methodology tends to be a dynamic form and in line with the new models proposed by the Ministry of Education in its Common Basic National Curriculum document and the State Secretariat of Education, Sport and Leisure of Mato Grosso, and also as provided in the Curricular Reference Document for Mato Grosso. Active learning methods become mandatory not only in specific activities, but also in activities integrated into the curriculum, instigating us to propose the use of some elements of the Integrative Education model in the context of STEAM as a possibility of transdisciplinary restructuring of practices for high school, which allows students to create and experience knowledge. In this context, it was proposed as a general objective, develop research that results in guidelines for the use of the active methods in the STEAM approach, and also that makes it possible to understand the complexity of the contemporary world, so as to enable thinking for a paradigmatic transition in the high school level. Thus, along the year 2019, an Integrative Investigative Didactic Sequence was developed with high school students and teachers of this school located in Cuiabá municipality, a reference in the State of Mato Grosso among students, considering the knowledge areas employed in STEAM approach (Sciences, Technology, Engineering, Arts and Mathematics), focusing on transdisciplinary biological aspects, employing the city of Cuiabá as a Potential Didactic Unit, reinforcing the use of non-schooled learning spaces. The results showed that STEAM is a promising approach for both biology teaching and other areas of knowledge, especially those that complement it, considering the data obtained in the evaluations of the proposal made by students and teachers from different areas of knowledge.